PAMELA SUE ANDERSON – WITNESS TO THE GOSPEL, PROPHET TO THE CHURCH: what might the church hear from her work?. Issue 1 (3rd March 2020) - Durber, Susan
Abstract: Pamela had, throughout her life, an ambivalent relationship with the church. She wanted her work to make a difference to it and she was committed to being a feminist philosopher of religion. There are many recurrent themes in her work that clearly relate to her background in the church, and particularly in the Lutheran church of her upbringing. Her challenge to the patriarchy of what she called "hyper-traditional" Christianity is clear, but also her critique of some forms of forgiveness and her search for new understandings of love and vulnerability. Her work presents significant challenges to the church, but does not abandon it, instead offering new ways of connecting with some of its most profound and important teachings and themes. Her work encourages us women in the church to value our own life experience as a source of knowledge, to re-frame our vulnerabilities and to find love in ways that offer freedom and hope. Pamela saw her work as her own contribution to the community of the church. It remains important that her voice, even and especially with its "speaker vulnerability, " is heard in that place.